O dolo como conhecimento e vontade no delito de lavagem de dinheiro : limites penais à imputação dolosa na legislação brasileira - Anacleto, Daniel Hartz (2022)
The present research has as object of study the intent in the crime of money laundering. More precisely, the main objective is to verify whether the intentional imputation of the crime of money laundering in Brazil is correct, dispensing with the agent's volitional element. In order to reach the main objective and respond to that problem, this research has as secondary objectives to identify which are the main theories dedicated to differentiating intent and guilt, to observe which are the main criticisms pointed out by cognitive and volitional theories, to describe the criteria required for the configuration of fraud in the crime of money laundering (restricted to art. 1, caput, of Law nº 9.613/98) and point out the solutions offered by the doctrine for criminal cases in which it is not identified (at least in a safe way) the will of the agent in the crime of money laundering. The adopted method is the hypothetical-deductive one, using national and comparative bibliographical research and documental research with reference to the general and special criminal legislation, considering especially the Brazilian Penal Code and Law nº 9.613, of March 03, 1998 and analysis of court cases. Research finds that proof of intent (even if measured from objective elements) should not be understood as a standardization of intent in order to disregard the volitional element of the subject's intimacy, under penalty of even rejecting the human condition of the agent. Thus, if there is no certainty as to the existence of the agent's will, one cannot speak of willful imputation of the money laundering crime, which must result in the atypicality of the conduct.